Effects of seed size and frugivory degree on dispersal by Neotropical frugivores - Fuzessy, Lisieux Franco [UNESP] (2018)
Large vertebrates are important elements of mutualistic interactions and provide positive impacts on plant population and community dynamics. Despite the increasing interest on vertebrate frugivory we are still not able to disentangle the real contribution of seed dispersal to Neotropical forest functioning. Consuming fruits does not imply effective seed dispersal and many variables, such as seed size and animal diet, may influence the outcome of plant-animal interactions. Here, we performed a comprehensive literature search on seed dispersal by Neotropical vertebrates (with a focus on primates) to closely approach their role as seed dispersers, hypothesizing frugivory degree and seed size as main drivers of fruit handling behavior and diversity of dispersed seeds. We found that the great majority of seeds manipulated by Neotropical primates, with exception to the seed predators pitheciins, were swallowed and passed intact through their gut. Larger seeds (> 12 mm) tended of being ingested exclusively by primates and other large vertebrates, such as tapirs and peccaries. Furthermore, primate feeding guild had a great influence on the richness and sizes of seeds dispersed, as primarily frugivores dispersed more species and had higher probabilities of ingesting larger seeds when compared to other feeding guilds. Organizing available knowledge and filling the main knowledge gaps allowed us to validate common sense assumptions and ultimately draw new conclusions about the role played by primates together with other major frugivores in Neotropical forests.